Protein adsorption resistant degradable polymer as well as preparation method and application thereof

By preparing a block polymer with carbon-carbon double bond functional group blocked, combining polyethylene glycol and hydrophobic chain segments, a multi-block polymer is formed, which solves the problem of medical implants adsorbing blood proteins in the body and achieves high-efficiency anti-protein Adsorption and excellent mechanical properties are suitable for a variety of processing methods.

CN119264404AActive Publication Date: 2025-01-07ZHEJIANG UNIV

Patent Information

Application Number
CN202411368628.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-07
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

Existing medical implants are prone to adsorb blood proteins after contacting blood in the body, resulting in coagulation and inflammatory reactions. Hydrophilic coating materials with high hydration capacity are insufficient in terms of mechanical strength and toughness, making them difficult to widely use.

Method used

Block polymers with carbon-carbon double bond functional groups are prepared by polymerization and capping reactions, combining specific polyethylene glycol blocks and hydrophobic chain segments to form multi-block polymers, and PEG chain segments are used to form hydration. The layer prevents protein adsorption and improves the chemical stability and mechanical properties of the material through crosslinking.

Benefits of technology

It has achieved significant improvement in protein adsorption properties under extremely small amounts of polyethylene glycol content, ensuring the processability and mechanical properties of the material. Its application range is greater than that of traditional materials, and is suitable for a variety of processing methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264404A_ABST
    Figure CN119264404A_ABST
Patent Text Reader

Abstract

The invention discloses a degradable polymer capable of resisting protein adsorption, a preparation method of the degradable polymer and application of the degradable polymer in preparation of a protein adsorption resisting material. The degradable polymer comprises the following raw materials: an initiator, a monomer and a double-bond terminated molecule. The degradable polymer is a block polymer terminated by a carbon-carbon double bond functional group, and the forming process of the degradable polymer comprises the following steps: carrying out polymerization reaction on a monomer under the action of an initiator or under the combined action of the initiator and a catalyst to obtain a first block polymer; and the first block polymer and the double-bond end-capping molecule are subjected to an end-capping reaction. The initiator comprises at least one of hydroxyl-terminated polyethylene glycol and n-arm polyethylene glycol, n is greater than or equal to 3, and the number-average molecular weights of the polyethylene glycol and the n-arm polyethylene glycol are respectively and independently 100-10000 g / mol. The mass ratio of the polyethylene glycol block in the degradable polymer is 5%-50%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of biomedical materials, and in particular to a degradable polymer resistant to protein adsorption and a preparation method and application thereof. Background Art

[0002] Medical implants have played an important role in the fields of cardiovascular and orthopedics as a treatment method. However, after foreign implants enter the body and come into contact with blood or body fluids, they will absorb proteins in the blood or body fluids in a very short time, thereby being recognized by the body's immune cells and triggering a series of foreign body reactions. Taking vascular implants as an example, cardiovascular stents undergo significant plasma protein adsorption within a few minutes after implantation. These adhered plasma proteins will quickly recruit platelet adsorption and trigger a rapid coagulation reaction; further, a large number of platelet adsorption will recruit the adhesion and infiltration of white blood cells in the blood, thereby triggering subsequent inflammatory reactions (Torii, S., Jinnouchi, H., Sakamoto, A., et al. Drug-eluting coronary stents: insights from preclinical and pathology studies [J]. Nat Rev Cardiol: 2019, 17 (1): 37-51). Therefore, cardiovascular implants require long-term anticoagulant therapy and anti-inflammatory response therapy during and after implantation. In addition, protein adsorption can cause bacteria to colonize on the surface of implants in vivo, which can also lead to infection or even severe reactions such as bacteremia on the surface of implants. Therefore, the anti-protein adsorption function of the implant surface is very important.

[0003] Currently, in clinical applications, hydrophilic coatings with high hydration capacity (such as phosphorylcholine coatings, polyethylene glycol coatings, etc.) are important methods to achieve anti-protein adsorption on implant surfaces (Wang, Z., Scheres, L., Xia, H., et al. Developments and Challenges in Self-Healing Antifouling Materials [J]. Advanced Functional Materials: 2020, 30 (26): 1908098). Among them, polyethylene glycol (PEG) molecular brush technology has been widely studied and used to prepare hydrophilic anti-protein adsorption surfaces. PEG forms a hydration layer on the surface of the material through its excellent hydrophilicity and strong water binding ability, thereby preventing nonspecific adhesion of proteins, platelets, bacteria, etc. However, the performance of this anti-protein adsorption surface based on molecular brush technology is highly dependent on the modification density and uniformity of the molecular brush. Only molecular brush coatings with high grafting density, close arrangement and uniform distribution can achieve anti-fouling effects. Any tiny defects on the surface of the material may make the design of the anti-fouling coating invalid. Therefore, in order to achieve high-density preparation of PEG molecular brush coatings on the surface of materials, complex physical and chemical modifications of the base materials are often required in research. These modification methods increase the preparation cost of the surface anti-protein adsorption coating on the one hand, and are not suitable for most chemically inert polymer materials on the other hand. At the same time, when these materials with high hydration capacity are used as bulk materials, they can only form hydrogel materials due to their extremely strong hydrophilicity, and their mechanical strength and toughness are weak, which seriously limits their use as functional implants in the body. Therefore, a simple preparation, wide range of application, and adjustable mechanical strength anti-protein adsorption bulk material and surface coating material and technology are still important technical bottlenecks. Summary of the invention

[0004] In view of the above technical problems and the deficiencies in the art, the present invention provides a degradable polymer resistant to protein adsorption and a preparation method and application thereof.

[0005] The specific technical solutions are as follows:

[0006] [1] A degradable polymer that resists protein adsorption, wherein the raw material composition of the degradable polymer includes an initiator, a monomer and a double-bond-terminated molecule.

[0007] The degradable polymer is a block polymer terminated with a carbon-carbon double bond functional group, and its formation process includes: 1) the monomer undergoes a polymerization reaction under the action of the initiator or under the combined action of the initiator and the catalyst to obtain a first block polymer; 2) the first block polymer undergoes a capping reaction with the double bond capping molecule.

[0008] The initiator includes at least one of polyethylene glycol with a hydroxyl terminal group and n-arm polyethylene glycol, where n≥3, and the number average molecular weight of the polyethylene glycol and the n-arm polyethylene glycol is independently 100 to 10000 g / mol. Considering the synthesis performance and processing capacity, in order to take into account the excellent anti-protein adsorption function, it is preferably 800 to 4000 g / mol, such as 1000 g / mol, 2000 g / mol, etc.

[0009] The mass proportion of the polyethylene glycol block in the degradable polymer is 5%-50%, preferably 8%-40%, such as 10%, 30%, etc. Such a strict molecular structure proportion setting mainly considers two factors: 1. As a material / coating resistant to protein adsorption, the coverage of the hydrated PEG chain has a great influence on the performance of the material. If the PEG content is too low, the hydration layer cannot completely cover the surface of the material / coating, which will cause the material / coating to fail; 2. However, when the PEG content is too high, the overall material is in a highly water-absorbing state in an underwater environment due to its strong hydrophilicity, and the PEG molecular chain loses its tightly packed structure due to swelling and straightening, and cannot effectively resist protein adsorption (such as adsorption). Figure 1 As shown), and the overall material exhibits poor toughness.

[0010] The monomer includes at least one of glycolide, L-lactide, mixed lactide, glycolic acid, lactic acid, ε-caprolactone, 1,4-dioxane-2-one, trimethylene carbonate, and polyhydroxyalkanoate.

[0011] The double bond-terminated molecule includes at least one of methacryloyl chloride, ethacryloyl chloride, and isocyanoethyl methacrylate.

[0012] The catalyst may include at least one of stannous octoate and dibutyltin dilaurate.

[0013] The amount of the catalyst used may be 0.01% to 0.5% of the total mass of the monomer and the initiator.

[0014] The reaction temperatures of the polymerization reaction and the end-capping reaction may be independently 120 to 160°C.

[0015] The reaction time of the polymerization reaction may be 1 to 10 hours.

[0016] To ensure the degree of end-capping of the carbon-carbon double bonds, the amount of the double bond end-capping molecule may be 1.1 to 3 times the molar amount of the hydroxyl group in the initiator, taking into account the chemical reactivity of different end-capping groups.

[0017] The polymerization reaction may be ring-opening polymerization, direct polycondensation, etc. Ring-opening polymerization is the polymerization of cyclic monomers after ring opening under the action of an initiator or an initiator and a catalyst; direct polycondensation refers to the reaction of generating polymers through repeated condensation reactions between bifunctional and / or multifunctional monomers, including melt polycondensation, solution polycondensation, interfacial polycondensation, solid phase polycondensation, etc.

[0018] [2] The method for preparing a degradable polymer according to [1], comprising the steps of:

[0019] S1, polymerizing the monomer under the action of the initiator or under the combined action of the initiator and the catalyst to obtain a first block polymer;

[0020] S2, subjecting the first block polymer to a capping reaction with the double bond capping molecule.

[0021] [3] Use of the degradable polymer described in [1] in the preparation of anti-protein adsorption materials.

[0022] When the degradable polymer is used to make anti-protein adsorption materials, it can be applied to a variety of purposes such as bulk materials and coating materials. For example: when used for bulk materials, products of specific shapes can be obtained through conventional polymer processing methods such as molding, extrusion, injection molding, casting and 3D printing. The cross-linkable carbon-carbon double bonds at both ends of the molecule can be internally cross-linked by heating or ultraviolet light to ensure the chemical stability of the product; for the needs of coating, different coating methods can be selected to apply the mixed solution containing the degradable polymer to the surface of the material, and the coating method includes but is not limited to ultrasonic atomization spraying, solution dipping, spin coating, etc. The thickness of the mixed solution coated on the surface of the material can be 0.1 to 50 μm.

[0023] The anti-protein adsorption and anti-fouling properties of the degradable polymer described in the present invention and the mechanism by which it can be made into an anti-protein adsorption material are as follows: the multi-block polymer is composed of hydrophilic PEG segments and hydrophobic segments. After forming a material / coating and ultraviolet cross-linking, the polymer will form a phase-separated structure on the surface of the material / coating, and the hydrophilic PEG segments will be stably exposed on the surface and form a firm hydration layer on the surface through hydrogen bonding, thereby hindering the adhesion of proteins, platelets and bacteria on the surface of the material / coating.

[0024] [4] A protein adsorption resistant material comprising the degradable polymer described in [1].

[0025] The anti-protein adsorption material may include an anti-protein adsorption coating. Further, the anti-protein adsorption coating may include the degradable polymer.

[0026] [5] The method for preparing the anti-protein adsorption material according to [4], comprising:

[0027] The degradable polymer and the free radical initiator are dissolved in a solvent to obtain a mixed solution, which is cross-linked and solidified by ultraviolet light and / or heating to obtain the anti-protein adsorption material.

[0028] The solvent may include at least one of dichloromethane, chloroform, hexafluoroisopropanol, ethyl acetate, and acetone.

[0029] In the mixed solution, the mass fraction of the degradable polymer may be 0.1% to 50%.

[0030] The free radical initiator may include at least one of a thermal initiator and a photoinitiator, and specifically include at least one of azobisisobutyronitrile (AIBN), benzoyl peroxide (BPO), benzophenone (BP), and I2959.

[0031] The amount of the free radical initiator used may be 0.1% to 5% of the mass of the degradable polymer.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] a) The present invention strictly limits the molecular weight of polyethylene glycol (PEG) and the content of polyethylene glycol blocks in the overall molecule: the number average molecular weight of PEG is 800-4000 g / mol, and the mass of PEG is 8%-40% of the total mass of the overall polymer; and a free radical initiator is used to initiate the carbon-carbon double bond end group to form a cross-linked polymer material. This unique molecular structure ensures that the polyethylene glycol is evenly distributed and each hydrophobic cross-linking point forms an orderly and tight stacking structure with each other, thereby significantly improving the anti-fouling ability. Based on this unique molecular structure design, the anti-protein adsorption material prepared by the present invention can achieve a protein adsorption amount less than or equal to the adsorption amount of the pure hydrophilic molecules tightly arranged material at a very low polyethylene glycol content, thereby ensuring the excellent processability and mechanical properties of the bulk material. It should be noted that the present invention focuses on limiting the specific polyethylene glycol molecular weight and content, rather than the material synthesis method. This type of block copolymer prepared by any other method is within the scope of protection of the present invention.

[0034] b) Compared with the traditional diblock copolymer based on polyethylene glycol monomethyl ether, the present invention strictly limits the PEG to the middle part of the hydrophobic segment in the material configuration. The unique molecular structure design of the present invention ensures that the PEG segment of the material has a more regular arrangement configuration and entropy elasticity in the underwater environment, so it has significantly better anti-protein adsorption performance (such as adsorption) than the diblock polymer with the same mass ratio. Figure 2 shown).

[0035] c) The anti-protein adsorption polymer material obtained by the present invention has good processability. The main material can be obtained by molding, extrusion, injection molding, casting and 3D printing, and the anti-adsorption coating can also be prepared by processing methods such as dipping and spraying. Therefore, its applicability is far greater than most anti-protein adsorption materials on the market. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is the effect of different PEG contents on the anti-plasma protein adsorption performance of the material;

[0037] Figure 2 This is a comparison chart of the anti-plasma protein adsorption performance of diblock and triblock polymer materials;

[0038] Figure 3 This is a comparison chart of the anti-platelet adhesion performance of the base material TPU, the coating of comparative example 1 and the coating of example 1;

[0039] Figure 4 Comparison of bacterial adhesion on the surface of TPU substrate material and PCEC208 coating;

[0040] Figure 5 This is a diagram of cell adhesion on the surface of the base material TPU and the anti-cell adhesion material PLEL210. DETAILED DESCRIPTION

[0041] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.

[0042] Unless otherwise specified, molecular weight units are g / mol.

[0043] Example 1

[0044] PLA-PEG-PLA-110 (PLEL110) biodegradable anti-protein adsorption material and coating preparation

[0045] (1) Synthesis of double bond terminated block polymers:

[0046] A 1L glass reactor was vacuum dried at 80°C for 1h, and 5g of polyethylene glycol with a number average molecular weight of 1000 was heated to 120°C and vacuum dried for 2h under nitrogen protection. Then, 45g of mixed racemic lactide was added to the reactor under nitrogen protection, and 50mg of stannous octoate was added, and the temperature was raised to 150°C. The reaction was carried out at 150°C and nitrogen protection for 5h, and then 0.1g of inhibitor 4-methoxyphenol was added. After uniform stirring for 30min, 1.6g of isocyanoethyl methacrylate was added dropwise to obtain a double-bond terminated block polymer (PLEL-110) with a number average molecular weight of about 10,000.

[0047] (2) Preparation of biological antifouling coating:

[0048] The PLEL110 obtained in step (1) was dissolved in dichloromethane, and a photoinitiator BP was added to prepare a mixed solution. The mass fraction of PLEL110 in the mixed solution was 20%, and the mass fraction of the photoinitiator BP was 0.2%. A coating with a thickness of 10 μm was prepared by dip coating. The coating was then cross-linked by ultraviolet irradiation, and the irradiation light intensity was 50 mW / cm 2 , irradiation time 3min.

[0049] According to the synthesis steps and coating preparation method of Example 1, PEG feed 5g was kept unchanged, and 95g, 45g, 11.7g and 5g of mixed racemic lactide were added to the reactor respectively to obtain degradable polymer coatings with polyethylene glycol block weight percentage of 5%, 10%, 30% and 50%. The anti-plasma protein adsorption performance of these polymer coatings was tested using a quartz crystal microbalance (QCM). The results are as follows: Figure 1 As shown, the degradable polymer with a polyethylene glycol block ratio of 10% has the best anti-protein adsorption performance.

[0050] Comparative Example 1

[0051] Preparation of PEG-PLA-110 (PEL110) diblock degradable anti-protein adsorption material and coating

[0052] (1) Synthesis of double bond terminated block polymers:

[0053] A 1L glass reactor was vacuum dried at 80°C for 1h, and 5g of polyethylene glycol monomethyl ether with a number average molecular weight of 1000 was heated to 120°C and vacuum dried for 2h under nitrogen protection. Then, 45g of mixed racemic lactide was added to the reactor under nitrogen protection, and 50mg of stannous octoate was added, and the temperature was raised to 150°C. The reaction was carried out at 150°C and nitrogen protection for 5h, and then 0.1g of inhibitor 4-methoxyphenol was added. After uniform stirring for 30min, 0.8g of isocyanoethyl methacrylate was added dropwise to obtain a double-bond terminated block polymer (PEL-110) with a number average molecular weight of about 10,000.

[0054] (2) Preparation of biological antifouling coating:

[0055] The PEL110 obtained in step (1) was dissolved in dichloromethane, and a photoinitiator BP was added to prepare a mixed solution. The mass fraction of PEL110 in the mixed solution was 20%, and the mass fraction of the photoinitiator BP was 0.2%. A coating with a thickness of 10 μm was prepared by dip coating. The coating was then cross-linked by ultraviolet irradiation, and the irradiation light intensity was 50 mW / cm2 , irradiation time 3min.

[0056] The anti-plasma protein adhesion performance of the coating materials of Example 1 and Comparative Example 1 was tested using QCM. The results are as follows: Figure 2 As shown, the amount of plasma protein adsorbed on the surface of the coating of Example 1 is significantly lower than that of the coating material of Comparative Example 1.

[0057] The control substrate (TPU), the coating of Example 1 and the coating material of Comparative Example 1 were respectively co-treated with platelet-rich plasma for 2 hours, and then washed, fixed, ethanol-dehydrated and gold-sprayed, and the platelets adhered to the surface were observed using a scanning electron microscope (SEM). Figure 3 The left, middle and right are SEM images of platelet adhesion on the control substrate (TPU), the coating of comparative example 1 and the coating of example 1. It can be seen that the control TPU substrate has more significant platelet adsorption, the platelet adhesion on the comparative coating has a certain decrease, and the surface of the coating of example 1 has no platelet adhesion at all, which proves that the coating of example 1 has better anti-protein adsorption and cell adhesion performance than the coating of comparative example 1.

[0058] Example 2

[0059] Preparation of PCL-PEG-PCL-208 (PCEC208) degradable and protein-resistant material

[0060] (1) Synthesis of double bond terminated block polymers:

[0061] A 1L glass reactor was vacuum dried at 80°C for 1h, and 20g of polyethylene glycol with a number average molecular weight of 2000 was heated to 80°C and vacuum dried for 2h under nitrogen protection. Then, 60g of ε-caprolactone was added to the reactor under nitrogen protection atmosphere and the temperature was raised to 120°C. Then, 30mg of stannous octoate was added under nitrogen protection atmosphere, the temperature was raised to 140°C, and the reaction was carried out at 140°C and nitrogen protection for 4h, and then 50mg of inhibitor 4-methoxyphenol was added. After uniform stirring for 30min, 3.5g of isocyanoethyl methacrylate was added dropwise to obtain a double-bond terminated block polymer (PCEC208) with a number average molecular weight of about 5000.

[0062] (2) Preparation of biological antifouling coating:

[0063] The PCEC208 obtained in step (1) was dissolved in ethyl acetate, and a photoinitiator I2959 was added to prepare a mixed solution. The mass fraction of PCEC208 in the mixed solution was 5%, and the mass fraction of the photoinitiator I2959 was 0.05%. The coating was prepared by ultrasonic spraying technology, and the obtained coating thickness was 10 μm. The coating was then cross-linked by ultraviolet irradiation, and the irradiation light intensity was 50 mW / cm2 , irradiation time 5min.

[0064] The base material of Example 2 and the coating material of Example 2 were incubated with Gram-positive bacteria Staphylococcus aureus (Sa) and Gram-negative bacteria Pseudomonas aeruginosa (Pa) for 4 hours, respectively, and then washed and stained with a bacterial live-dead stain. Figure 4 This is the amount of bacteria adhesion on the surface of the base material TPU and the bio-antifouling coating PCEC208 of Example 2. It can be found that there is basically no bacteria adhesion on the coating surface.

[0065] Example 3

[0066] Preparation of degradable and protein-resistant material of PLA-PEG-PLA-210 (PLEL210)

[0067] (1) Synthesis of double bond terminated block polymers:

[0068] A 1L glass reactor was vacuum dried at 80°C for 1h, and 20g of polyethylene glycol with a number average molecular weight of 2000 was heated to 120°C and vacuum dried for 2h under nitrogen protection. Then 80g of DL-lactide was added to the reactor and vacuum dried at 120°C for 1h. Then 80mg of stannous octoate was added, the temperature was raised to 150°C, and the reaction was carried out at 150°C under nitrogen protection for 6h, and then 0.5g of inhibitor 4-methoxyphenol was added. After uniform stirring for 30min, 3.5g of isocyanoethyl methacrylate was added dropwise to obtain a double-bond terminated block polymer with a number average molecular weight of about 10,000.

[0069] (2) Preparation of anti-cell adhesion materials:

[0070] The PLEL210 obtained in step (1) was dissolved in dichloromethane, and the photoinitiator I2959 was added to prepare a mixed solution. The mass fraction of PLEL210 in the mixed solution was 20%, and the mass fraction of the photoinitiator was 0.2%. The film material was prepared by solution casting technology, and then the coating was cross-linked by ultraviolet irradiation, and the irradiation light intensity was 50mW / cm 2 , irradiation time 5min.

[0071] Live cell stained endothelial cells (EC), smooth muscle cells (SMC), mouse embryonic cells (3T3) and macrophages (THP-1) were inoculated on the base material of Example 3 and the material of Example 3, respectively, and observed under a fluorescence microscope after incubation for 8 hours. Figure 5 The cell adhesion amount of the base material TPU and the surface PLEL210 of the anti-cell adhesion material in Example 3 shows that the PLEL210 material significantly reduces the adhesion of different types of cells, providing a good basis for reducing inflammatory response after material implantation.

[0072] Example 4

[0073] Preparation of degradable and protein-resistant PLA-PEG-PLA-105 (PLEL105) material

[0074] A 1L glass reactor was vacuum dried at 80°C for 1h, and 10g of polyethylene glycol with a number average molecular weight of 1000 was heated to 120°C and vacuum dried for 2h under nitrogen protection. Then 40g of DL-lactide was added to the reactor and vacuum dried at 120°C for 1h. Then 50mg of stannous octoate was added, the temperature was raised to 150°C, and the reaction was carried out at 150°C under nitrogen protection for 3h, and then 0.5g of inhibitor 4-methoxyphenol was added. After uniform stirring for 30min, 3.5g of isocyanoethyl methacrylate was added dropwise to obtain a double-bond terminated block polymer (PLEL105) with a number average molecular weight of about 5000.

[0075] Example 5

[0076] Preparation of PLGA-PEG-PLGA-108 (PLGELG-108) biodegradable anti-protein adsorption material

[0077] A 1L glass reactor was vacuum dried at 80°C for 1h, and 10g of polyethylene glycol with a number average molecular weight of 1000 was heated to 120°C and vacuum dried for 2h under nitrogen protection. Then 35g of L-lactide and 50mg of stannous octoate were added, the temperature was raised to 150°C, and the reaction was carried out at 150°C under nitrogen protection for 1h; then 35g of glycolide was added to the reactor, and the temperature was raised to 160°C, and the reaction was continued for 3h under nitrogen protection, and then 0.2g of inhibitor 4-methoxyphenol was added, and after uniform stirring for 30min, 3.5g of isocyanoethyl methacrylate was added by dropwise addition to obtain a double-bond terminated block polymer (PLGELG-108) with a number average molecular weight of about 8000.

[0078] Example 6

[0079] Preparation of PTMC-PEG-PTMC-212 (PTET-212) degradable anti-protein adsorption material

[0080] A 1L glass reactor was vacuum dried at 80°C for 1h, and 20g of polyethylene glycol with a number average molecular weight of 2000 was heated to 120°C and vacuum dried for 2h under nitrogen protection. Then, 100g of trimethylene carbonate was added to the reactor under nitrogen protection, and 0.1g of stannous octoate was added, and the temperature was raised to 150°C. The reaction was carried out at 150°C and nitrogen protection for 5h, and then 0.2g of polymerization inhibitor 4-methoxyphenol was added. After uniform stirring for 30min, 3.5g of isocyanoethyl methacrylate was added dropwise to obtain a double-bond terminated block polymer (PTET-212) with a number average molecular weight of about 12000.

[0081] Example 7

[0082] Preparation of PLCL-PEG-PLCL-112 (PLCELC-112) degradable and protein-resistant material

[0083] A 1L glass reactor was vacuum dried at 80°C for 1h, and 10g of polyethylene glycol with a number average molecular weight of 1000 was heated to 120°C and vacuum dried for 2h under nitrogen protection. Then, 55g of DL-lactide and 55g of ε-caprolactone were added to the reactor under nitrogen protection, and 0.1g of stannous octoate was added, and the temperature was raised to 150°C. The reaction was carried out at 150°C and nitrogen protection for 5h, and then 0.2g of inhibitor 4-methoxyphenol was added. After uniform stirring for 30min, 3.5g of isocyanoethyl methacrylate was added dropwise to obtain a double-bond terminated block polymer (PLCELC-112) with a number average molecular weight of about 12000.

[0084] Example 8

[0085] Preparation of PPDO-PEG-PPDO-420 (PDED-420) biodegradable anti-protein adsorption material

[0086] A 1L glass reactor was vacuum dried at 80°C for 1h, and 40g of polyethylene glycol with a number average molecular weight of 4000 was heated to 120°C and vacuum dried for 2h under nitrogen protection. Then, 160g of 1,4-dioxane-2-one was added to the reactor under nitrogen protection, and 0.5g of stannous octoate was added, and the temperature was raised to 140°C. The reaction was carried out at 140°C and nitrogen protection for 4h, and then 0.5g of inhibitor 4-methoxyphenol was added. After uniform stirring for 30min, 3.5g of isocyanoethyl methacrylate was added dropwise to obtain a double-bond terminated block polymer (PDED-420) with a number average molecular weight of about 20,000.

[0087] In addition, it should be understood that after reading the above description of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.

Claims

1. A degradable polymer resistant to protein adsorption, characterized in that: The raw material composition of the degradable polymer includes an initiator, a monomer and a double-bond-terminated molecule; The degradable polymer is a block polymer terminated with a carbon-carbon double bond functional group, and its formation process includes: 1) the monomer undergoes a polymerization reaction under the action of the initiator or under the combined action of the initiator and the catalyst to obtain a first block polymer; 2) the first block polymer undergoes a capping reaction with the double bond capping molecule; The initiator comprises at least one of polyethylene glycol with a hydroxyl terminal group and n-arm polyethylene glycol, wherein n≥3, and the number average molecular weight of the polyethylene glycol and the n-arm polyethylene glycol is independently 100 to 10000 g / mol, preferably 800 to 4000 g / mol; The mass proportion of the polyethylene glycol block in the degradable polymer is 5%-50%, preferably 8%-40%; The monomer includes at least one of glycolide, L-lactide, mixed lactide, glycolic acid, lactic acid, ε-caprolactone, 1,4-dioxane-2-one, trimethylene carbonate, and polyhydroxyalkanoate; The double bond-terminated molecule includes at least one of methacryloyl chloride, ethacryloyl chloride, and isocyanoethyl methacrylate.

2. The degradable polymer according to claim 1, characterized in that The catalyst includes at least one of stannous octoate and dibutyltin dilaurate; The amount of the catalyst used is 0.01% to 0.5% of the total mass of the monomer and the initiator.

3. The degradable polymer according to claim 1, characterized in that The reaction temperatures of the polymerization reaction and the end-capping reaction are independently 120 to 160° C.; The reaction time of the polymerization reaction is 1 to 10 hours.

4. The degradable polymer according to claim 1, characterized in that The amount of the double bond-terminated molecule used is 1.1 to 3 times the molar amount of the hydroxyl group in the initiator.

5. The method for preparing a degradable polymer according to any one of claims 1 to 4, characterized in that: Includes steps: S1, polymerizing the monomer under the action of the initiator or under the combined action of the initiator and the catalyst to obtain a first block polymer; S2, subjecting the first block polymer to a capping reaction with the double bond capping molecule.

6. Use of the degradable polymer according to any one of claims 1 to 4 in the preparation of anti-protein adsorption materials.

7. A protein adsorption resistant material, characterized in that: The degradable polymer comprises the degradable polymer according to any one of claims 1 to 4.

8. The protein-adsorption resistant material according to claim 7, characterized in that: The anti-protein adsorption material includes an anti-protein adsorption coating; The anti-protein adsorption coating comprises the degradable polymer.

9. The method for preparing the protein-adsorption resistant material according to claim 7 or 8, characterized in that: include: The degradable polymer and the free radical initiator are dissolved in a solvent to obtain a mixed solution, which is cross-linked and solidified by ultraviolet light and / or heating to obtain the anti-protein adsorption material.

10. The method for preparing the anti-protein adsorption material according to claim 9, characterized in that: The solvent includes at least one of dichloromethane, chloroform, hexafluoroisopropanol, ethyl acetate, and acetone; In the mixed solution, the mass fraction of the degradable polymer is 0.1% to 50%; The free radical initiator includes at least one of a thermal initiator and a photoinitiator, specifically including at least one of azobisisobutyronitrile, benzoyl peroxide, benzophenone, and I2959; The amount of the free radical initiator used is 0.1% to 5% of the mass of the degradable polymer.

Citation Information

Patent Citations

  • Temperature induction self healing porous material, and preparation method and application thereof

    CN106867020A

Cited By

  • Application of degradable polymer in preparation of endothelialization functional material

    CN120733130A

  • Use of a degradable polymer in the preparation of an endothelialized functional material

    CN120733130B